2016
DOI: 10.1088/1742-5468/2016/07/073301
|View full text |Cite
|
Sign up to set email alerts
|

Many-body-localization transition: strong multifractality spectrum for matrix elements of local operators

Abstract: For short-ranged disordered quantum models in one dimension, the Many-Body-Localization is analyzed via the adaptation to the Many-Body context [M. Serbyn, Z. Papic and D.A. Abanin, PRX 5, 041047 (2015)] of the Thouless point of view on the Anderson transition : the question is whether a local interaction between two long chains is able to reshuffle completely the eigenstates (Delocalized phase with a volume-law entanglement) or whether the hybridization between tensor states remains limited (Many-Body-Locali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 131 publications
7
48
1
Order By: Relevance
“…The fact that multifractality occurs also in the many-body localized phase is in agreement with the analysis of matrix elements of local operators and the statistics of hybridization ratios in nearest-neighbors many-body localized models [46].…”
Section: Multifractal Spectrum F Criti (α) At the Critical Point B C =supporting
confidence: 85%
See 4 more Smart Citations
“…The fact that multifractality occurs also in the many-body localized phase is in agreement with the analysis of matrix elements of local operators and the statistics of hybridization ratios in nearest-neighbors many-body localized models [46].…”
Section: Multifractal Spectrum F Criti (α) At the Critical Point B C =supporting
confidence: 85%
“…For a quantum one-dimensional toy model, we have analyzed the statistical properties of the rare extensive resonances that are needed to destabilize the many-body localized phase. At criticality, we have found that the entanglement entropy can grow with an exponent 0 < α = 3/2 − a < 1 anywhere between the area law α = 0 and the volume law α = 1, as a function of the power law exponent a of the couplings (Equation (79)), while the entanglement spectrum follows the strong multifractality statistics of Equation (101), well-known as the "strong-multifractality" spectrum in the context of Anderson localization transition [47] and found recently for nearest-neighbor MBL models at criticality [46].…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations